2019
DOI: 10.1093/eurheartj/ehz746.1020
|View full text |Cite
|
Sign up to set email alerts
|

P6426The use of direct oral anti-coagulations (DOACs) compared to vitamin k antagonist in patients with left ventricular thrombus after acute myocardial infarction

Abstract: Aim Current guidelines recommend the use of Vitamin K Antagonist (VKA) for up to 3–6 months for the treatment of LV thrombus post- acute myocardial infarction (AMI). However based on evidence supporting the non-inferiority and potential superiority of Direct Oral Anti-Coagulation's (DOAC) compared to VKA for other indications such as atrial fibrillation, DOACs are being increasingly used off licence for the treatment of left ventricular (LV) thrombus post AMI. In this study we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Finally, thirteen articles were included in the synthetic analysis, two of which were prospective studies [5][6][7][8][9][16][17][18][19][20][21][22][23].…”
Section: Characteristics and Quality Assessment Of The Included Studiesmentioning
confidence: 99%
“…Finally, thirteen articles were included in the synthetic analysis, two of which were prospective studies [5][6][7][8][9][16][17][18][19][20][21][22][23].…”
Section: Characteristics and Quality Assessment Of The Included Studiesmentioning
confidence: 99%
“…In six studies reporting clinically relevant bleedings 6,9,16,22,24,25 , NOACs users showed more favorable outcomes (RR: 0.35, 95% CI: 0.13-0.92, P = 0.03; I 2 = 0, Figure 2E ), and no significant publication bias was detected by the funnel plot ( Supplementary figure 1E ). Age did not affect the difference in clinically relevant bleeding risk between NOACs and VKAs (RR: 0.83, 95% CI:0.41-1.69, P = 0.516, Supplementary figure 3E ).…”
Section: Resultsmentioning
confidence: 92%
“…Eleven studies investigated the outcome of failure in thrombus resolution 5-9,16-19,21,22,24,25 , and the resolution rate was similar in two groups (RR: 0.88, 95% CI: 0.72-1.09, P = 0.20, Figure 2C ), with an low statistical heterogeneity (I 2 = 26%, P = 0.20) and no significant publication bias based on the funnel plot ( Supplementary figure 1C ) and statistical tests (Begg’s test, P = 0.484; Egger’s test, P = 0.191). Age did not show substantial impacts on thrombus resolution according to meta-regression (RR: 1.08, 95% CI: 0.95-1.22, P = 0.215, Supplementary figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations